Relacja Thomasa Plattera jako źródło do życia codziennego uczniów wrocławskich szkół na początku XVI wieku - Wójcik, Jacek (Biuletyn Historii Wychowania, 2016)
Thomas Platter (1499–1582) was a Swiss humanist, printer and writer. At the age of 72, he wrote his autobiography. He devoted a large part of his life to studies. He would travel from city to city, looking for thing to learn. He probably spent a few years (since 1516) in Wrocław. In his autobiography, he covered a lot of the time including students’ life. Platter noted that all lectures took place simultaneously in one room while the St. Elisabeth School library could offer one book. The students had a responsibility to sing in churches. In their free time, they would go to pubs and begged for money. The living conditions were very poor: many students slept on the floor in a single room or at the parish cemetery, plagued by rats and lice. Therefore they frequently fell sick. Platter cared about food and mentioned it very often in his memoirs; when he travelled sometimes there was nothing to eat but in the cities he happened to eat too much. The life of a traveling student in the 15th-16th centuries was very dangerous. Thomas Platter’s autobiography is a very important source of information, indicating all the obstacles to the process of learning in the early sixteenth century.